If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+14=8(x+1)
We move all terms to the left:
7x+14-(8(x+1))=0
We calculate terms in parentheses: -(8(x+1)), so:We get rid of parentheses
8(x+1)
We multiply parentheses
8x+8
Back to the equation:
-(8x+8)
7x-8x-8+14=0
We add all the numbers together, and all the variables
-1x+6=0
We move all terms containing x to the left, all other terms to the right
-x=-6
x=-6/-1
x=+6
| 1/2(x-8)=2x-2 | | x+54+x+22=180 | | -n+4=10+5n-5n | | x+70+96=180 | | 6=-2r+26 | | -16=-6-a | | 11+8p=-8p+5p | | x+59+100=180 | | –10+3j=–7j | | 5-6x=11-3x | | 168=8(5+x) | | 5=5-1n-2n | | 1008=(2x-6)(x+8) | | 11x-13=8x+11 | | x+65+x+71=180 | | n/9-6=-5 | | x+24+x+2=180 | | 7+4n=43 | | 2(11x-3(=104 | | 3x-4+x=4x-4 | | p/8=-10 | | X+13+x+13=180 | | -3(6-4x)=5x-18 | | 14x+22=11x+52 | | r-11=-19 | | 45+2x=21 | | -84+10x-3=21x+4 | | F(—1)=4x+11 | | 5-6x=6+2x | | 3(7x-4)-5(2x-1)=6 | | 2(8x-20)=8 | | 7976=8p+98 |